2017
DOI: 10.1016/j.jagp.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Negative Life Events and Widowhood on Risk for Dementia

Abstract: Objective The aim of the current study was to examine the effect of negative life events and widowhood on the incidence of dementia. Design and participants We used data from four Swedish longitudinal cohort studies with a total of nearly 2,000 participants and 8–25 years of follow-up. Measurements We examined seven stressful events for which data were available in all cohorts. Clinical dementia diagnoses were made through medical and psychological examinations. Cox proportional hazards models were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 45 publications
7
9
0
Order By: Relevance
“…In addition, given the mixed findings on the longitudinal link between widowhood and cognitive function, the present study considered both the changes in cognitive function over time and the rates of cognitive changes in relation to widowhood duration, which may be a unique contribution to the field. Consistent with previous research, we observed that the experience of widowhood was associated with the trajectories of cognitive decline among Korean older adults for up to 8 years of follow‐up. A significant duration effect on cognitive function was found in our unadjusted model, which suggests that the first 2 years after spousal loss was associated with a lower level of cognitive function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, given the mixed findings on the longitudinal link between widowhood and cognitive function, the present study considered both the changes in cognitive function over time and the rates of cognitive changes in relation to widowhood duration, which may be a unique contribution to the field. Consistent with previous research, we observed that the experience of widowhood was associated with the trajectories of cognitive decline among Korean older adults for up to 8 years of follow‐up. A significant duration effect on cognitive function was found in our unadjusted model, which suggests that the first 2 years after spousal loss was associated with a lower level of cognitive function.…”
Section: Discussionsupporting
confidence: 91%
“…All covariates were significantly associated with cognitive function (P < 0.001).Figure 2shows the longitudinal relationship between widowhood status and cognitive function trajectory after controlling for covariates (model 4).4 | DISCUSSIONGiven the limited research evidence regarding the longitudinal impact of widowhood on changes in cognitive function among the Korean population, the present study investigated the effects of widowhood status on the trajectories of cognitive function among communitydwelling older adults in Korea from a nationally representative dataset.In addition, given the mixed findings on the longitudinal link between widowhood and cognitive function, the present study considered both the changes in cognitive function over time and the rates of cognitive changes in relation to widowhood duration, which may be a unique contribution to the field. Consistent with previous research,20,[38][39][40] we observed that the experience of widowhood was associated with the trajectories of cognitive decline among Korean older adults for up to 8 years of follow-up. A significant duration effect on cognitive function was found in our unadjusted model, which suggests that the first 2 years after spousal loss was associated with a lower level of cognitive function.…”
supporting
confidence: 91%
“…This study found a greater risk of dementia developing among widowed people, in case-control and cross-sectional studies, compared with cohort studies 11 . These results confirm the findings of the present study, which exhibited a greater occurrence of dementia among widowed people, which links widowhood to greater conditions of stress and less social support for dealing with daily activities 12 .…”
Section: Discussionsupporting
confidence: 92%
“…In other words, patients who become widow are at higher risk for dementia. Previous studies have validated this, which shows that experience of a stressful life event is associated with an increased risk of dementia [ 7 ]. Also, the AD8 shows that those individuals with high education (six years or more) were at a lower risk of dementia (p < 0.01).…”
Section: Discussionsupporting
confidence: 56%